Towards self-organized service-oriented multi-agent systems - Leitão, Paulo (2014)
The demand for large-scale systems running in complex and even chaotic environments requires the consideration of new paradigms and technologies that provide flexibility, robustness, agility and responsiveness. Multiagents systems is pointed out as a suitable approach to address this challenge by offering an alternative way to design control systems, based on the decentralization of control functions over distributed autonomous and cooperative entities. However, in spite of their enormous potential, they usually lack some aspects related to interoperability, optimization in decentralized structures and truly self-adaptation. This paper discusses a new perspective to engineer adaptive complex systems considering a 3-layer framework integrating several complementary paradigms and technologies. In a first step, it suggests the integration of multi-agent systems with service-oriented architectures to overcome the limitations of interoperability and smooth migration, followed by the use of technology enablers, such as cloud computing and wireless sensor networks, to provide a ubiquitous and reconfigurable environment. Finally, the resulted service-oriented multi-agent system should be enhanced with biologically inspired techniques, namely self-organization, to reach a truly robust, agile and adaptive system.